Mediating the power of Buddhas : ritual in the Maǹjuʹsrimūlakalpa - Wallis, Glenn (SUNY series in Buddhist studies., 2002)
"Mediating the Power of Buddhas offers a fascinating anaylsis of the seventh-century ritual manual, the Manjusrimulakalpa. This medieval text is intended to reveal the path into a ritual universe where the power of a buddha abides. Author Glenn Wallis traces the strategies of the Manjusrimulakalpa to enable its committted reader to perfect the promised ritual, uncovering what conditions must be met for ritual practice to succeed and what personal characteristics practitioners must possess in order to realize the ritual intentions of the Buddhist community. The manual itself was written at a key point in Buddhist history, one when Hindu forms of practice were still imitated and on the cusp of the shift from Mahayana to Vajrayana (or Tantric) Buddhism. In addition, the Manjusrimulakalpa presents a rich compendium of Buddhist life in an earlier era, containing information on a variety of its readers' concerns: astrology, astronomy, medicine and healing, ritual practice, iconography, devotion, and meditation."--Jacket